A Comparison of Efficacy between Rebamipide and Omeprazole in the Treatment of NSAIDs Gastropathy - Suyata Suyata; Erita Bustami; Syadra Bardiman; Fuad Bakry (The Indonesian Society for Digestive Endoscopy, 2004)
Background: Gastropathy represent a disparity of gastric mucosal characterized by sub-epithelial bleeding and erosion. Gastropathy can be induced by non steroidal anti-inflammatory drugs (NSAIDs), alcohol, stressor, and chemical agents with various sign and symptoms. NSAIDs-induced gastropathy is the second most common etiology of gastric ulcer and variceal haemorrhages. Aims: To investigate the effectivity of rebamipide compare with omeprazole in treatment of NSAIDs- induced gastropathy. Method: This triple blind randomized study was enrolled from January to June 2004 with 38 subjects who were recruited from outpatient and inpatient clinic in M Hoesin Hospital in Palembang. Subject was divided into two groups. Endoscopic examination was performed in every patients. Results: There was an improvement of symptom in rebamipide group (78.9%) and omeprazole group (79.0%) after treatment but it didn’t have significant difference statistically. Improvement of NSAIDs induced gastropathy after treatment between two groups have significant difference (P = 0.02), and improvement of gradation of gastropathy after treatment has significant difference (P = 0.007).There was no side effect of administration of rebamipide and omeprazole in each group. Conclusion: Rebamipide as effective as omeprazole in improvement of symptom. Omeprazole is more effective than rebamipide in improvement of NSAIDs induced gastropathy and is as safe as rebamipide in the treatment of NSAIDs induced gastropathy. Keywords: Gastropathy, NSAIDs, rebamipide, omeprazole